HUBUNGAN ANTARA SARANA LABORATORIUM TERHADAP KETERAMPILAN PROSES SAINS SISWA KELAS XI MIPA 5 DI SMA NEGERI 3 KOTA BENGKULU - Nola Desti Pratiwi Simanjuntak; Salastri Rohiat; Elvinawati Elvinawati (University of Bengkulu, 2017)
[RELATIONSHIP BETWEEN LABORATORY FACILITIES AND STUDENT PROCESS SKILLS AT CLASS XI MIPA 5 IN SMA NEGERI 3 KOTA BENGKULU] The purpose of this study was to determine the relationship of laboratory facilities to students' science process skills in the laboratory. This research is a correlational research. The population in this study is all students of class XI MIPA 5 academic year 2016/2017 in SMA Negeri 3 Kota Bengkulu. This research uses total sampling technique so that the entire population is used as research sample. The independent variable (x) in this research is chemical laboratory equipment and dependent variable (y) is the science process skill of students in laboratory of SMA Negeri 3 Kota Bengkulu.. Data collection in this research using questionnaire instrument with 30 items and observation sheet with 15 items . Technique of data analysis using expert validity test, questionnaire analysis, observation analysis of science process skill, normality test, linearity test, correlation analysis and hypothesis test. Data analysis using the help of SPSS 16 program. The results of data processing correlation coefficient (r) obtained that is equal to 0.387 at 5% significance level. . The result of hypothesis test shows that Ha is accepted which means there is a significant correlation between laboratory facilities and science process skill of students in laboratory on chemistry learning of students of class XI MIPA 5 SMA Negeri 3 Kota Bengkulu academic year 2016/2017